A steroid receptor coactivator small molecule “stimulator” attenuates post-stroke ischemic brain injury - McClendon, Lisa K.; Garcia, Roberto L.; Lazaro, Tyler; Robledo, Ariadna; Vasandani, Viren; Luna, Zean Aaron Evan; Rao, Abhijit S.; Srivatsan, Aditya; Lonard, David M.; Dacso, Clifford C.; Kan, Peter; O’Malley, Bert W. (Frontiers in Molecular Neuroscience, 2022)
Introduction: Pathologic remodeling of the brain following ischemic stroke results in neuronal loss, increased inflammation, oxidative stress, astrogliosis, and a progressive decrease in brain function. We recently demonstrated that stimulation of steroid receptor coactivator 3 with the small-molecule stimulator MCB-613 improves cardiac function in a mouse model of myocardial ischemia. Since steroid receptor coactivators are ubiquitously expressed in the brain, we reasoned that an MCB-613 derivative (MCB-10-1), could protect the brain following ischemic injury. To test this, we administered MCB-10-1 to rats following middle cerebral artery occlusion and reperfusion. Methods: Neurologic impairment and tissue damage responses were evaluated on day 1 and day 4 following injury in rats treated with control or 10-1. Results: We show that 10-1 attenuates injury post-stroke. 10-1 decreases infarct size and mitigates neurologic impairment. When given within 30 min post middle cerebral artery occlusion and reperfusion, 10-1 induces lasting protection from tissue damage in the ischemic penumbra concomitant with: (1) promotion of reparative microglia; (2) an increase in astrocyte NRF2 and GLT-1 expression; (3) early microglia activation; and (4) attenuation of astrogliosis. Discussion: Steroid receptor coactivator stimulation with MCB-10-1 is a potential therapeutic strategy for reducing inflammation and oxidative damage that cause neurologic impairment following an acute ischemic stroke.